Adlai E. Stevenson address - Stevenson, Adlai E. (Adlai Ewing), 1900-1965.
Typescript of an address given by Stevenson at the Emancipation Proclamation centennial ceremonies at the Lincoln Memorial, Washington, D.C., September 22, 1962.
Diplomat, governor of Illinois, public official, and lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- President (1861-1865 : Lincoln). -- Anniversaries, etc; African Americans -- Civil rights; Lincoln Memorial (Washington, D.C.); Diplomats; Governors -- Illinois; Lawyers; Public officials -- Illinois